2008
DOI: 10.1177/0269881108091252
|View full text |Cite
|
Sign up to set email alerts
|

Hyperprolactinemia and possibly related development of prolactinoma during amisulpride treatment; three cases

Abstract: Schizophrenia is a chronic and debilitating psychotic mental disorder that affects about 1% of the world's population. Antipsychotic drugs are the mainstay of treatment in schizophrenia. Hyperprolactinemia, which is a common side effect of typical antipsychotics, is also associated with the use of some of the newer atypical agents. Antipsychotics may enhance prolactinoma growth as manifested by an increase in serum prolactin concentration. Prolactin-secreting pituitary adenomas possibly related with antipsycho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
24
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(38 citation statements)
references
References 21 publications
1
24
0
Order By: Relevance
“…On the contrary, partial D2 agonists, such as ARI, BRE, and CAR, can lower prolactin levels, even below drug-free baseline, and adjunctive ARI has been shown to decrease hyperprolactinemia associated with other antipsychotics 28,209211. Several cases have been reported describing antipsychotic use and prolactinoma,212 in particular in cases using AMI213,214 or RIS 215–217. However, no solid data are available, and thus, no conclusions can be drawn on the association of antipsychotics and prolactinoma 218…”
Section: Methodsmentioning
confidence: 99%
“…On the contrary, partial D2 agonists, such as ARI, BRE, and CAR, can lower prolactin levels, even below drug-free baseline, and adjunctive ARI has been shown to decrease hyperprolactinemia associated with other antipsychotics 28,209211. Several cases have been reported describing antipsychotic use and prolactinoma,212 in particular in cases using AMI213,214 or RIS 215–217. However, no solid data are available, and thus, no conclusions can be drawn on the association of antipsychotics and prolactinoma 218…”
Section: Methodsmentioning
confidence: 99%
“…A recent case series is suggestive that amisulpride may also be associated with the development of prolactinomas mediated via hyperprolactinaemia. 61 Neither clinical studies nor epidemiologic studies conducted to date have shown a definitive association between chronic administration of this class of drugs and tumorigenesis in humans; the available evidence is considered too limited to be conclusive at this time. .........................................................................................................................................…”
Section: Longer Term Consequences Of Hyperprolactinaemia Bonementioning
confidence: 99%
“…The US Food and Drug Administration Adverse Event Reporting System pharmacovigilance database study strongly linked risperidone (adjusted reporting ratio 18.7) with the highest frequency of pituitary adenomas compared with haloperidol (5.6), ziprasidone (3.0) and olanzapine (2.3) (Szarfman et al, 2006). A recent case series is suggestive that amisulpride may also be associated with the development of prolactinomas mediated via hyperprolactinaemia (Akkaya et al, 2009). The multiple actions of prolactin and relative lack of research into hyperprolactinaemia suggest that additional potential long-term effects may be discovered potentially in glands such as the thyroid.…”
Section: Possible Association With Cancermentioning
confidence: 99%